Impact of conditioning intensity on outcomes of haploidentical stem cell transplantation for patients with acute myeloid leukemia 45 years of age and over. Issue 9 (8th January 2019) - Santoro, Nicole; Labopin, Myriam; Ciceri, Fabio; Van Lint, Maria Teresa; Nasso, Daniela; Blaise, Didier; Arcese, William; Tischer, Johanna; Bruno, Benedetto; Ehninger, Gerhard; Koc, Yener; Santarone, Stella; et al.
Abstract : Background: T cell–replete haploidentical stem cell transplantation (haplo‐SCT) is a valid therapeutic option for adult patients with high‐risk acute myeloid leukemia (AML) lacking an HLA‐matched sibling or unrelated donor. Method: We retrospectively analyzed the outcomes of 912 AML patients ≥45 years of age who had undergone haplo‐SCT with either myeloablative conditioning (MAC; n = 373) or reduced intensity conditioning (RIC; n = 539) regimens. Results: The median follow‐up was 31.1 and 25.7 months for MAC and RIC, respectively. The incidence of relapse and nonrelapse mortality (NRM) were 25.1% versus 28.7% and 31.0% versus 30.3% for MAC and RIC, respectively; 2‐year leukemia‐free survival (LFS) was 43.9% for MAC versus 41.0% for RIC. In multivariate analysis, the use of MAC versus RIC was not associated with a difference in the outcomes. Results were confirmed in the propensity score–weighted analysis. Disease status and performance status at transplantation were associated with outcomes. Notably, the use of posttransplantation cyclophosphamide was associated with reduced acute graft‐versus‐host disease (aGVHD) stage III‐IV, and NRM and increased overall survival, LFS, and GVHD‐free, relapse‐free survival. The use of mobilized peripheral blood stem cells was associated with an increased risk of stage II‐IV aGVHD. Conclusion: No differences were found between MAC and RIC regimens for haplo‐SCT in adults with AML who were ≥45 years of age. The type of GVHD prophylaxis, disease status, and performance status were the major predictors of transplantation outcome. These results may serve as the background for randomized study comparing RIC versus MAC for haplo‐SCT in adults with AML. Abstract : The outcomes of 912 acute myeloid leukemia patients ≥45 years of age undergoing haploidentical stem cell transplantation with either myeloablative conditioning (MAC) or reduced‐intensity conditioning (RIC) show no impact of the regimen intensity. Both MAC and RIC are suitable preparative regimens, and the choice should be evaluated on a case‐by‐case basis according to patients and disease characteristics.